2023
DOI: 10.1021/acssuschemeng.2c06572
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Thermal Reduction of CuInS2 Quantum Dot-Sensitized Bi2MoO6 Hierarchical Flowers on S-Doped Biochar for Dual Z-Scheme/Mott–Schottky Heterojunction Construction: A Strategy for Efficient Photocatalytic Biorefineries

Abstract: In this work, an S-doped biochar-supported CuInS2 quantum dot-sensitized Bi2MoO6 hierarchical flower (CIS@BMO@SL) was prepared using a bottom-up technique. The partial thermal reduction of CuInS2 quantum dot-sensitized Bi2MoO6 successfully fabricated a dual heterojunction, which is composed of CuInS2/Bi2MoO6 Z-scheme and Bi/Bi2MoO6 Mott–Schottky heterojunctions. The dual heterojunction was identified by X-ray photoelectron spectroscopy (XPS) and high-resolution transmission electron microscopy. Under the syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The curve-fitted Al 2p XPS spectrum shows two peak components with BEs at 74.0 and 75.1 eV, corresponding to the Al 2p 3/2 and Al 2p 1/2 of Al 3+ cations . Similarly, as shown in Figure d,e, the deconvoluted Ga 2p and In 3d spectra both show two peaks, confirming the presence of Ga 3+ (Ga 2p 3/2 at 1145.1 eV and Ga 2p 1/2 at 1118.2 eV) and In 3+ (In 2p 3/2 at 452.4 eV and In 2p 1/2 at 444.8 eV) ions, respectively. , These XPS results provide further evidence of the existence of Group-IIIA metal ions (Al 3+ , Ga 3+ , or In 3+ ) in the M-TiO 2 samples. Taken together, considering the XRD, SEM, and XPS findings, it can be concluded that successful construction of group IIIA metal-doped TiO 2 has been achieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The curve-fitted Al 2p XPS spectrum shows two peak components with BEs at 74.0 and 75.1 eV, corresponding to the Al 2p 3/2 and Al 2p 1/2 of Al 3+ cations . Similarly, as shown in Figure d,e, the deconvoluted Ga 2p and In 3d spectra both show two peaks, confirming the presence of Ga 3+ (Ga 2p 3/2 at 1145.1 eV and Ga 2p 1/2 at 1118.2 eV) and In 3+ (In 2p 3/2 at 452.4 eV and In 2p 1/2 at 444.8 eV) ions, respectively. , These XPS results provide further evidence of the existence of Group-IIIA metal ions (Al 3+ , Ga 3+ , or In 3+ ) in the M-TiO 2 samples. Taken together, considering the XRD, SEM, and XPS findings, it can be concluded that successful construction of group IIIA metal-doped TiO 2 has been achieved.…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent that the work function (Φ) of the Group-IIIA metal-doped samples is smaller than that of the pristine TiO 2 , indicating that the electrons of the former are more favorable to transfer than that of the latter. 46 Meanwhile, Figure 6e illustrates that the positions of the valence band (E VB vs E Fermi ) of the pristine TiO 2 , Al-TiO 2 , Ga-TiO 2 , and In-TiO 2 photocatalysts are 2.12, 2.10, 2.08, and 1.98 eV, respectively. Therefore, the valence band potentials (E VB vs NHE) and conduction band potentials (E CB vs NHE) of the samples were determined by using eqs 3 and 4 , respectively, in combination with the results obtained from UV-Vis DRS (Figure 6e).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring and utilizing clean and sustainable resources is one of the best resolutions to the intensifying environmental problems and energy crisis. Biomass photoreforming powered by solar energy provides a promising strategy, where the redox potential of the photocatalysts is fully utilized to coproduce green fuels and high-value chemicals . Nevertheless, a majority of the traditional photocatalysts are still confined by the narrow photoabsorption range, fast charge carrier recombination, and low product selectivity, resulting in unsatisfactory photocatalytic activity. , Biochar materials have captured a sea of attention due to their versatile physicochemical properties, including high electrical conductivity, high surface area, optical absorption, as well as chemical and thermal stability. A pressing need is obvious for the rational design of low-cost biochar (BC)-based photocatalysts with enlarged solar light response and enhanced photoinduced carrier separation, accompanied by the selective liquid product formation. , …”
Section: Introductionmentioning
confidence: 99%